Research Methodology in the Management Sciences - Aboubakere HAJI; Toufik MAJDI; Issam IZZA (Communications of International Proceedings, 2022)
Epistemology highlights the rules of knowledge production on which all academic research is based. Far from being reduced to a simple methodology, the study of the epistemology of research appeals to deeper notions such as the scientificity of knowledge, the approach by which it is produced, its scientific scope. In this spirit, our work seeks to initiate researchers in management sciences on the epistemology of research and its different paradigms. Our goal is to enlighten them on the three main epistemological postures and above all to remind them of the need to produce work that combines rigor with relevance.
Keywords: Epistemology; methodology; positivism; interpretivism; constructivism